Enemy aliens, prisoners of war : internment in Canada during the Great War - Kordan, Bohdan S. (McGill-Queen's studies in ethnic history. Series 2., 2002)
"In Enemy Aliens, Prisoners of War Bohdan Kordan assesses the policy and practice of civilian internment in Canada during the Great War and provides a clear but critical analysis of the complex nature of this experience. Period photographs and first person accounts augment the text, helping to communicate the human drama of the story. A comprehensive roster identifying those interned in the frontier camps of the Rocky Mountains is included."--Jacket